2023
DOI: 10.1001/jamanetworkopen.2023.20868
|View full text |Cite
|
Sign up to set email alerts
|

Association of Nighttime Speed Limits and Electric Scooter–Related Injuries

Rasmus Liukkonen,
Heljä Aarnikko,
Pekka Stenman
et al.

Abstract: This cohort study investigates whether nighttime speed restrictions are associated with the incidence of electric scooter–related injuries in Finland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…The primary aim of nighttime restrictions is to limit the number of intoxicated riders and therefore limit injuries, as alcohol use has been common in patients experiencing e-scooter injuries . To our knowledge, nighttime restrictions have only been examined in 2 studies, both of which did not find evidence of a difference after the introduction of the restrictions . In our study, the number of both nighttime and alcohol-related injuries decreased after implementing the restrictions.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…The primary aim of nighttime restrictions is to limit the number of intoxicated riders and therefore limit injuries, as alcohol use has been common in patients experiencing e-scooter injuries . To our knowledge, nighttime restrictions have only been examined in 2 studies, both of which did not find evidence of a difference after the introduction of the restrictions . In our study, the number of both nighttime and alcohol-related injuries decreased after implementing the restrictions.…”
Section: Discussionmentioning
confidence: 51%
“…Although it was impossible to adjust these phenomena, we consider the total effect of these to be minor compared with the restrictions. In Tampere, Finland, a city with a similar population, health care system, and behavioral habits to Helsinki, the incidence of injuries remained fairly the same between 2019 and 2021, when there were no major restrictions . In addition, Williams et al reported that the number of monthly rides and e-scooter–related emergency department visits correlated well, and there was no detectable decrease or increase in the monthly injury incidence during their study period from August 2018 to December 2019.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In addition, there were no barriers to the time or location of riding. Over time a variety of safety initiatives have decreased the dangers of e‐scooters with features such as speed limits, 6 curfews, 7 geofencing 8 and the availability of helmets 9 being introduced. Traffic separation however remains a major issue with e‐scooters being either ridden on the road with similar risks experienced by cyclists, or on the footpath where pedestrians represent a constant hazard both to themselves and to the riders who crash into them.…”
mentioning
confidence: 99%